Christianity in the twentieth century : a world history - Stanley, Brian, 1953- (Princeton, Princeton University Press, 2018)
"Christianity in the Twentieth Century charts the transformation of one of the world's great religions during an age marked by world wars, genocide, nationalism, decolonization, and powerful ideological currents, many of them hostile to Christianity. Written by a leading scholar of world Christianity, the book traces how Christianity evolved from a religion defined by the culture and politics of Europe to the expanding polycentric and multicultural faith it is today--one whose growing popular support is strongest in sub-Saharan Africa, Latin America, China, and other parts of Asia."--Jacket
Chapter 1. Wars and rumors of wars: the response of British and American churches to the First World War. The global religious legacy of the First World War ; The British churches: the religious legacy of the First World War ; Fighting for the faith: American fundamentalism between the wars ; Divergent Christian responses -- Chapter 2. Holy nations? Uneasy marriages between Christianity and nationalism. Christianity and the diffusion of nationalism ; Protestant nationalism in Korea: Christianity, anticolonialism, and national identity ; Catholic nationalism in Poland: Mary as the queen of a dismembered nation ; Christianity and nationalism: uneasy bedfellows --
Includes bibliographical references (pages 429-469) and index
Keywords: Church history -- 20th century; Church history -- 20th century; Christianity -- History